Naija: The Cinderella for Nigerian and West African National Language, Unity and Identity - Omowumi Olabode Steven Ekundayo (MASI Mandiri Edukasi, 2022)
The perennial questions about the national language and the Nigerian Pidgin (Naija) status remain unresolved in Nigeria. Hence, this paper focuses on the national language question for Nigeria against the theoretical background of the national language, national identity, and linguistic relativism. The paper sets out to reevaluate the common arguments often articulated against adopting Naija as the national language and advance the reasons why it should be adopted as the national language. The paper adopted the qualitative approach to research. Primary data were generated from the interview, observation, and spontaneous speech recording, while secondary data were taken from library materials and the Internet. Educated and illiterate Nigerians constituted the study population, and mixed and purposive sampling methods were used to select informants. It is established in this paper that it is the de facto national language and the most undermined and neglected among the five major languages in Nigeria. The paper concludes that language, a critical factor of production, has been undermined. Adopting Naija as a national language will foster national unity and cohesion, accelerate scientific advancement, facilitate democratization and enhance teaching and learning in the long run.